1982
DOI: 10.1111/j.1365-2125.1982.tb01359.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the angiotensin converting enzyme inhibitor, captopril, in essential hypertension.

Abstract: 1 The effects of the orally active angiotensin converting enzyme inhibitor, captopril, were examined in 15 patients with mild or moderate essential hypertension. 2 Following initial dosing with captopril 25 mg, there was a significant fall in supine and erect blood pressure in 2 h and lasting for 6 h. There was no significant alteration of heart rate. No reduction was seen in plasma noradrenaline concentration. Maximum inhibition of plasma converting enzyme activity occurred 60 min post‐dosing. 3 There was a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
1

Year Published

1982
1982
1992
1992

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 19 publications
3
7
1
Order By: Relevance
“…However, this phenomenon is unlikely to be a serious problem in our experiments where captopril was administered only once, although a slight and transient decrease in angiotensinogen has been reported after a single dose of enalapril (Millar et al, 1982 Regarding the lack of correlation between PCEA inhibition and DBP reduction, Waeber et al (1980) also found a discrepancy between captopril-induced PCEA inhibition and PRA increase on the one hand and the drug's antihypertensive effect on the other and concluded that BP response to captopril was not completely accounted for by the renin-angiotensin system inhibition. In contrast, Campbell et al (1982) found a strong correlation between BP reduction and PCEA inhibition, but it must be pointed out that in their experiments a low dose (25 mg) of captopril was used which did not induce a complete PCEA blockade while in our experiments and those by Waeber et al (1980) an almost complete PCEA inhibition was obtained. Finally, the lack of correlation between the fall in DBP and the pre-captopril PRA values in our experiments is probably due to the fact that such a correlation can only be found when large numbers of subjects from all three renin subgroups are analyzed as shown by Gavras et al (1981).…”
Section: Correlationscontrasting
confidence: 41%
See 1 more Smart Citation
“…However, this phenomenon is unlikely to be a serious problem in our experiments where captopril was administered only once, although a slight and transient decrease in angiotensinogen has been reported after a single dose of enalapril (Millar et al, 1982 Regarding the lack of correlation between PCEA inhibition and DBP reduction, Waeber et al (1980) also found a discrepancy between captopril-induced PCEA inhibition and PRA increase on the one hand and the drug's antihypertensive effect on the other and concluded that BP response to captopril was not completely accounted for by the renin-angiotensin system inhibition. In contrast, Campbell et al (1982) found a strong correlation between BP reduction and PCEA inhibition, but it must be pointed out that in their experiments a low dose (25 mg) of captopril was used which did not induce a complete PCEA blockade while in our experiments and those by Waeber et al (1980) an almost complete PCEA inhibition was obtained. Finally, the lack of correlation between the fall in DBP and the pre-captopril PRA values in our experiments is probably due to the fact that such a correlation can only be found when large numbers of subjects from all three renin subgroups are analyzed as shown by Gavras et al (1981).…”
Section: Correlationscontrasting
confidence: 41%
“…However, the correlation between blood pressure reduction and converting enzyme inhibition remains controversial (Waeber et al, 1980;Campbell et al, 1982). Furthermore, because reliable plasma assay of captopril has for long not been available, the possible relationships between the drug's pharmacokinetics, its effects on the renin-angiotensin-aldosterone system and its antihypertensive properties have not yet been studied simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Decreased sympathetic tone may therefore be an alternative explanation for the absence of reflex tachycardia during captopril therapy. Plasma noradrenaline levels, however, have been found not to be depressed during angiotensin-converting enzyme inhibition (Campbell et al, 1981;Zanella et al, 1981;Millar et al, 1982). Furthermore, the absence of alteration in the circulatory reflexes mediated by Valsalva's manoeuvre in the present study provides further evidence that there is no interaction between captopril and the autonomic nervous system.…”
Section: Discussionsupporting
confidence: 60%
“…The hypotensive effect of captopril is probably due largely to withdrawal of the potent pressor effect of angiotension II (Ferguson et al, 1977) although other mechanisms may be involved (Cranz et al, 1979;Marks et al, 1980;Zimmerman, 1981;Imai et al, 1982). Vasodilator drugs such as hydralazine when given alone reduce peripheral vascular resistance but lead to secondary baroreflex-mediated tachycardia, whereas angiotensin-converting enzyme inhibition by captopril causes a fall in blood pressure without associated changes in heart rate in animals (Clough et al, 1979), normotensive man and hypertensive patients (Campbell et al, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…The treatment was generally well tolerated. The combination with a diuretic not only made captopril more effective in patients who at first showed no response to it (Brunner et al, 1978;Brunner et al, 1979;Johnston et al, 1979;Aguglia et al, 1981;Campbell et al, 1982) but the diuretic also permitted a lower dose of the drug itself. Such a reduction probably reduces its side effects.…”
Section: Discussionmentioning
confidence: 99%